Polysaccharide Extraction from Defatted Rambutan Seeds with Hot Water and Subcritical Water Extractions - Kamonthip Nilmat; Somkiat Ngamprasertsith; Winatta Sakdasri; Pinit Jirukkalul; Aphichart Karnchanatat; Sajee Noitang; Ruengwit Sawangkeaw (My University, 2023)
Rambutan seeds (RS) are industrial waste often generated in the canned fruit industry. The aim of this study was to extract polysaccharides from defatted rambutan seeds or crude polysaccharides (POLS-DRSs) with subcritical water. Defatted seed powder (DRS) was extracted by hot-water extraction (HWE) at 100 °C as a reference condition. Subcritical water extraction (SWE) was performed at 120–140 °C and an initial pressure of 2 MPa. A sample-to-water ratio of 1:10 (w/w) and an extraction time of 15–60 min were used for both methods. The results show that gravimetric extraction yields of 53.01 g/100 g DRS and 7.71–41.70 g/100 g DRS were obtained from HWE and SWE, respectively. Additionally, HWE provided a total sugar content of 30.75 g/100 g POLS-DRSs, while SWE generated a total sugar content in the range of 27.00–49.76 g/100 POLS-DRSs. The antioxidant activities of POLS-DRSs were measured with a 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. An amount of 40 mg of POLS-DRSs obtained at 120 °C after 60 min provided the highest DPPH activity of 82.93% inhibition. The POLS-DRSs were suitable for growing microorganisms because they had a high sugar content and a low total phenolic content. A prebiotic activity assay will be carried out in future studies.
Keywords: Rambutan; Hot water extraction; Water extraction; Reducing sugar; Polysaccharides Composition and Applications